RESPONE OF SILVER KING PEACH TRANSPLANTS TO SULPHUR AND PHOSPHORUS FERTILIZER AT DEFERNT SIZES OF ROOTSTOCKS - Sulaiman M. Kako (Mesopotamia Journal of Agriculture)
This study was conducted on peach transplants (Prunus persica Batsch) in the Nursery of Technical Institute / Mosul /Iraq, during 2007 growing seasons ,to investigate the effect of sulphur and phosphorus on Silver King Peach transplants, which was budded on Peach seedling rootstocks at different sizes on available soil concentrations of N,P , and K in the soil and this effect on leaves minerals content of Silver King Peach transplants, , agriculture sulphur and phosphorus. Three levels of sulphur (0 , 3.5 and 7grSˉ¹transplant) , three levels of Phosphorus (0, 1 and 2 grPˉ¹transplant) and three rootstocks ( 8,7, 6 mm ) respectively was used. The results indicated that the Sulphur , Phosphorus and the interaction between sulphur and phosphorus caused a significant increase in available concentration of N,P and K in the soil. The interaction between Sulphur and Phosphorus significantly affected the concentration of available nitrogen, phosphorus and potassium in the soil ,also the results indicated that the diameter rootstock , Sulphur , and Phosphorus and their interaction between them caused a significant increase in the concentration of N,K in the leaves .The interaction treatment of medium diameter+ 7 gm S transplantˉ¹ +2gm Pˉ¹ transplantˉ¹ was the best treatment as compared with the other treatments which gave the highest means of available concentrations of N,P ,K in the soil and their concentrations in the leaves .